Gas Diffusion Strategy for Inserting Atomic Iron Sites into Graphitized Carbon Supports for Unusually High‐Efficient CO2 Electroreduction and High‐Performance Zn–CO2 Batteries. Issue 29 (15th June 2020) - Wang, Tingting; Sang, Xiahan; Zheng, Wanzhen; Yang, Bin; Yao, Siyu; Lei, Chaojun; Li, Zhongjian; He, Qinggang; Lu, Jianguo; Lei, Lecheng; Dai, Liming; Hou, Yang
Abstract: Emerging single‐atom catalysts (SACs) hold great promise for CO2 electroreduction (CO2 ER), but the design of highly active and cost‐efficient SACs is still challenging. Herein, a gas diffusion strategy, along with one‐step thermal activation, for fabricating N‐doped porous carbon polyhedrons with trace isolated Fe atoms (Fe1 NC) is developed. The optimized Fe1 NC/S1 ‐1000 with atomic Fe‐N3 sites supported by N‐doped graphitic carbons exhibits superior CO2 ER performance with the CO Faradaic efficiency up to 96% at −0.5 V, turnover frequency of 2225 h −1, and outstanding stability, outperforming almost all previously reported SACs based on N‐doped carbon supported nonprecious metals. The observed excellent CO2 ER performance is attributed to the greatly enhanced accessibility and intrinsic activity of active centers due to the increased electrochemical surface area through size modulation and the redistribution of doped N species by thermal activation. Experimental observations and theoretical calculations reveal that the Fe‐N3 sites possess balanced adsorption energies of *COOH and *CO intermediates, facilitating CO formation. A universal gas diffusion strategy is used to exclusively yield a series of dimension‐controlled carbon‐supported SACs with single Fe atoms while a rechargeable Zn–CO2 battery with Fe1 NC/S1 ‐1000 as cathode is developed to deliver a maximal power density of 0.6 mW cm −2 . Abstract : A universal gas‐diffusion strategy is developed for fabricating a series of single‐atom catalysts with atomic Fe sites at trace amounts supported by dimension‐controlled graphitized carbons. Benefitting from highly catalytic active isolated Fe‐N3 sites and graphitic N species, the optimized Fe1 NC/S1 ‐1000 exhibits superior CO2 electroreduction activity and outstanding Zn–CO2 battery performance.